Fine-scale genetic structure of the threatened rosewood Dalbergia nigra from the Atlantic Forest: comparing saplings versus adults and small fragment versus continuous forest - Batista Leite, Fernanda Araújo; Brandão, Rosângela Luci; Buzatti, Renata Santiago de Oliveira; de Lemos-Filho, José Pires; Lovato, Maria Bernadete (Tree genetics & genomes, 2014)
Assessing the population genetic structure of threatened species is important for developing successful conservation strategies. In this study, we evaluated the fine-scale spatial genetic structure (SGS) of Dalbergia nigra from a regenerating secondary forest fragment and compared it with previous data from a primary forest of a large reserve. A total of 107 adult and 111 saplings were mapped and genotyped for seven microsatellite loci. The genetic diversity was high and similar in adults (H ₑ = 0.682) and saplings (H ₑ = 0.680). The spatial extent of SGS was higher in adults than in saplings. Overlapping generations in the potentially reproductive individuals is the likely explanation for the higher SGS in adults (Sp = 0.016) in relation to the saplings (Sp = 0.010). The SGS in the adults from the secondary forest fragment was similar to that found in the primary forest. Considering the SGS found in adults, from both the secondary and primary forests, seeds for ex situ conservation should be collected from trees at least 80 m apart to reduce the genetic similarity between samples. These results highlight the importance of preserving small forest fragments to allow successful regeneration and maintenance of the genetic diversity in D. nigra.